2003
DOI: 10.1055/s-2003-812405
|View full text |Cite
|
Sign up to set email alerts
|

Zementierte versus unzementierte Revisions-Hüftarthroplastik mit verdichtetem Knochenallograft - Prospektiv randomisierte Vergleichsstudie mit Jahres-Follow-up

Abstract: Cemented technique in hip revisions using morselized bone allograft is as good as uncemented technique in preserving BMD measured by the DEXA method and restoring function in a 5 years follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…(b) CT at 5 years and 6 months proves rigid fixation in all Gruen zones except in zone 1. randomizing Paprosky grade II patients into two groups intraoperatively, and comparing cementless impaction grafting using Corail stems with cemented impaction bone grafting using polished femoral stems. [4]. They concluded that functional scores and bone density around the femoral stem at up to five years were similar.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…(b) CT at 5 years and 6 months proves rigid fixation in all Gruen zones except in zone 1. randomizing Paprosky grade II patients into two groups intraoperatively, and comparing cementless impaction grafting using Corail stems with cemented impaction bone grafting using polished femoral stems. [4]. They concluded that functional scores and bone density around the femoral stem at up to five years were similar.…”
Section: Discussionmentioning
confidence: 97%
“…In a search of English literature, cementless impaction bone graft in revision THA is scarce [4,12], and there is only one English abstract described by German authors, (Figure 4) showed that the calcar allograft united to the host bone with partial absorption and it showed no further subsidence compared to 1-year X-ray. (b) CT at 5 years and 6 months proves rigid fixation in all Gruen zones except in zone 1. randomizing Paprosky grade II patients into two groups intraoperatively, and comparing cementless impaction grafting using Corail stems with cemented impaction bone grafting using polished femoral stems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study of BMD changes after uncemented rearthroplasty, Nesse et al (2003) presented a material where all patients received impacted bone allograft. They noted less proximal bone loss than we did, which may be due to the fact that we grafted only half of the patients.…”
Section: Discussionmentioning
confidence: 99%